DESAIN LKPD BERORIENTASI KOMPLEKSITAS KONTEN DAN PROSES KOGNITIF PADA MATERI GAYA PADA BAHAN ELASTIS UNTUK PEMBELAJARAN FISIKA SMA/MA - Vera Yunita; Amali Putra; Harman Amir (Universitas Negeri Padang, 2017)
The purpose of learning Physics is to develop knowledge and train students’thinking ability. It can occur when teachers actively engage the students in the learning process (student center). Therefore, teaching materials that can improve students’ competence is needed, such as worksheet.This research was aimed to produce a content complexity and cognitive process oriented worksheet, which is valid, practical, and effective to be used in teaching and learning Physics at SMA/MA. The type of the research was research and development with 4D development model (define, design, development and desseminate), which is reduced to be 3D. Desseminate phase was not implemented due to time and budget limitation. The research subject was a class of students. Moreover, the research procedure included front-end analysis, students’ need analysis, task analysis, concept analysis, learning objectives analysis, test preparation, media selection, format selection, making draft, expert validation, product revision, and limited testing. Further, instrument used for data collection was a validation sheet, sheet practicalities, students’ responses questionnaire also pretest and posttest. The result of this research, which is about content complexity and cognitive process oriented worksheet in material about forces on the elastic material, can be presented in two studies. First, worksheet is developed using the 4D model with the findings’ guided model syntax containing scientific approach. Second, the worksheet produced is located in the criteria of very valid and very practical to be used in teaching Physics with the respective values3.43 and 3.45 also effective to improve the knowledge of students.